Engagement in Pleasant Leisure Activities and Blood Pressure: A 5-Year Longitudinal Study in Alzheimer Caregivers. Issue 7 (September 2017) - Mausbach, Brent T.; Romero-Moreno, Rosa; Bos, Taylor; von Känel, Roland; Ziegler, Michael G.; Allison, Matthew A.; Mills, Paul J.; Dimsdale, Joel E.; Ancoli-Israel, Sonia; Losada, Andrés; Márquez-González, María; Patterson, Thomas L.; et al.
ABSTRACT: Objective: Elevated blood pressure is a significant public health concern, particularly given its association with cardiovascular disease risk, including stroke. Caring for a loved one with Alzheimer disease has been associated with physical health morbidity, including higher blood pressure. Engagement in adaptive coping strategies may help prevent blood pressure elevation in this population. This 5-year longitudinal study examined whether greater participation in pleasant leisure activities was associated with reduced blood pressure in caregivers. Methods: Participants were 126 in-home spousal Alzheimer's caregivers (M [SD] age = 74.2 [7.9] years) that completed five yearly assessments. Linear mixed-effects models analysis was used to examine the longitudinal relationship between pleasant leisure activities and caregivers' blood pressure, after adjusting for demographic and health characteristics. Results: Greater engagement in pleasant leisure activities was associated with reduced mean arterial blood pressure ( B = −0.08, SE = 0.04, p = .040). Follow-up analyses indicated that engagement in activities was significantly associated with reduced diastolic ( B = −0.07, SE = 0.03, p = .030) but not systolic blood pressure ( B = −0.10, SE = 0.06, p = .114). In addition, mean arterial blood pressure was significantly reduced when caregiving duties ended because of placement of care recipients in nursing homes ( B = −3.10, SE = 1.11, p = .005) or death of the care recipient ( B = −2.64, SE = 1.14, p = .021). Conclusions: Greater engagement in pleasant leisure activities was associated with lowered caregivers' blood pressure over time. Participation in pleasant leisure activities may have cardiovascular health benefits for Alzheimer's caregivers. Abstract : Supplemental digital content is available in the text.